THE EVALUATION OF THE EFFECT OF THE GROUPS NUMBER AND BREAKS IN THE CUMULATIVE PROCESS ON THE PARAMETER VALUE OF ACCUMULATION - Okorokov, A. M. (Science and Transport Progress, 2008)
The influence of quantity of wagon groups in a set of multi-group train and breaks in accumulation of train sets on fluctuations of the value of parameter of train set accumulation is considered.